After the waves : the impact of the tsunami on women in Sri Lanka - De Mel, Neloufer; Ruwanpura, Kanchana N.; Samarasinghe, Gameela; Social Scientists Association of Sri Lanka (Colombo : Social Scientists' Association, 2010)
Contributed articles on the women disaster victims of Sri Lanka and their rehabilitation issues.
Includes bibliographical references (p. 282-299).
Keywords: Women disaster victims -- Rehabilitation -- Sri Lanka; Tsunami relief -- Sri Lanka; Indian Ocean Tsunami, 2004.